A metal additively manufactured (MAM) heat exchanger for electric motor thermal control on a high-altitude solar aircraft – Experimental characterisation. (1st October 2020) - Wrobel, Rafal; Scholes, Ben; Hussein, Ahmed; Law, Richard; Mustaffar, Ahmad; Reay, David
Highlights: Heat exchangers have been designed for high-altitude solar-powered aircraft. The exchangers have been manufactured using metal additive manufacturing. This method has allowed highly compact and light weight units to be constructed. The heat transfer and pressure drop performance meet the design requirements. Abstract: This paper describes the development and experimental testing of a metal additively manufactured (MAM) integrated heat exchanger for cooling part of the electric propulsion system of a high-altitude solar-powered aircraft. The thermal management of electric motors designed for such an application is particularly difficult due to frequently conflicting design targets, such as high-level of integration, low-weight and high-heat removal capability. In this preliminary study, a number of cooling solutions were briefly considered before detail design of a MAM heat exchanger was carried out. The design target was to dissipate 250 W, the approximate heat load during take-off operation where the relatively high torque demand corresponds to a considerable power loss. As the heat exchanger is located downstream of the propeller, within the engine nacelle, CFD modelling was employed to examine the nature of the airflow upstream of the heat exchanger front face prior to the heat exchanger design. Wind tunnel tests were performed to measure the heat transfer and pressure drop characteristics. The heat exchanger design was based upon a novel surface concept that is not possible to be made with conventional manufacturing techniques as it combines involute secondary surface and 3D lattice structure as tertiary fins to maximise flow mixing and surface area. Two variants were constructed, the second iteration addressing the perceived excessive pressure drop of the first prototype. The tests demonstrated that the second design of heat exchanger met the required duty in terms of heat transfer and pressure drop, and that MAM allowed a high values of surface area/volume ratio without compromising the weight of the unit.